ADVANCED INTERNATIONAL PRACTICES IN VENTURE FINANCING OF INNOVATION PROJECTS - Vahobov Javohir Sobir o‘g‘li (Modern American Journals, 2025)
This article analyzes the established mechanisms and practical models of financing innovative venture projects in foreign countries, assessing their applicability within the context of Uzbekistan. Venture financing plays a crucial role in commercializing innovative ideas and integrating them into the market economy. The study explores the effective utilization of venture capital within the innovation ecosystems of developed countries such as the United States, European nations, and Japan. These international experiences can serve as a foundation for developing new mechanisms for financing scientific and practical innovation projects in Uzbekistan. Moreover, the paper highlights the significance of venture financing in improving national innovation policy, expanding private sector involvement, and fostering startup development.
Keywords: Venture financing, innovation ecosystems, venture capital funds, startup development, public-private partnerships, risk investment, intellectual property protection, financial infrastructure, international practices, economic modernization.